2016
DOI: 10.2174/1570162x14666161006121455
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes as an HIV Reservoir: Mechanism of HIV Infection

Abstract: If we have any hope of achieving a cure for HIV infection, close attention to the cell types capable of getting infected with HIV is necessary. Of these cell types, astrocytes are the most ideal cell type for the formation of such a reservoir. These are long-lived cells with a very low turnover rate and are found in the brain and the gastrointestinal tract. Although astrocytes are evidently resistant to infection of cell-free HIV in vitro, these cells are efficiently infected via cell-tocell contact by which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 0 publications
2
63
1
Order By: Relevance
“…Lastly, a contact with live, apoptotic or necrotic CD4 + T cells did not reverse virus latency. These data are in agreement with previous studies showing no increase in HIV‐1 production by LRAs in persistently infected astrocytes (Chauhan, ; Li et al, ). However, other studies reported some reactivation with bryostatin (Diaz et al, ), JQ1 and various HDAC inhibitors (Gray et al, ; Narasipura et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Lastly, a contact with live, apoptotic or necrotic CD4 + T cells did not reverse virus latency. These data are in agreement with previous studies showing no increase in HIV‐1 production by LRAs in persistently infected astrocytes (Chauhan, ; Li et al, ). However, other studies reported some reactivation with bryostatin (Diaz et al, ), JQ1 and various HDAC inhibitors (Gray et al, ; Narasipura et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, our data clearly demonstrate that HFA can be infected by X4‐tropic viruses through their contact with virus‐infected primary human CD4 + T cells. It has been proposed that HIV‐1 infection in astrocytes may be restricted when the infection is very low, a process that can be overcome when the entry barrier is bypassed by VSV‐G pseudotyping (Li et al, ). We recapitulated such a very low infection process by using either m7NDK pseudotypes or a coculture step with virus‐infected CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, astrocytes were shown to be capable of transmitting HIV to immune cells by cell‐to‐cell contact in co‐culture experiments (Li et al, ), suggesting that they also contribute to virus spread. For a more in‐depth discussion of the potential of astrocytes to form virus reservoirs and promote neurological damage to the brain and HAND, the reader is referred to selected reviews (Carroll & Brew, ; Gray, Brew, & Churchill, ; Li, Henderson, & Nath, ; Saylor et al, ).…”
Section: Introductionmentioning
confidence: 99%